NITRIC OXIDE: ROLE IN HUMAN BIOLOGY (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Nitric oxide (NO), a free radical, possesses various modulatory effects on biological systems. NO is synthesized from L-arginine by converting it to L-citrulline via nitric oxide synthase (NOS) enzymes. Moreover, various precursors of NO have been reported that include arginine, citruline, arginine alphaketoglutarate (A-AKG) and arginineketoisocaproate (A-KIC). NO possess various direct and indirect effects that broadly affect various tissues and organ systems inside the body. The present review article aims to discuss about the pharmacology, physiological roles and effects of NO.